Consecuencias penales para el profesional de contaduría pública por actos indebidos en Colombia. - Quintero Sisa, Julio César (Universidad Antonio Nariño, 2022)
The exercise of the accounting profession in Colombia in recent years has been strongly questioned by the errors and scams of which businessmen, ordinary people and even the state itself have been victims, this at the hands of accounting professionals who have not complied with their professional ethics and have left the profession very frowned upon.